Hex [videorecording (DVD)] - Rodionoff, Hans; Adams, Kayla; Holcomb, Matthew; Roberts, Bryan (Lionsgate, 2022)
Following a mysterious disappearance on a jump, a group of skydivers experience paranormal occurrences that leave them fighting for their lives.